Cultural Experience and Coexistence in Chile: Some Ideas from Intercultural Philosophy; [Vivencia y Convivencia Cultural en Chile: Algunas Ideas Desde la Filosofía Intercultural] - Gonzalez-Fuentes, L (University of San Buenaventura - Cali, 2024)
Intercultural philosophy has taken as its philosophical goal the coexistence between cul-tures and, within it, the question of whether people and communities of diverse traditions can understand each other and live together, transcending the act of sharing geographical limits in a given time. Indeed, intercultural philosophy has inquired into this coexistence in a more demanding sense than other naturalistic or political-philosophical currents, which have remained in the foundation of coexistence from human necessity or tolerance. The demand that intercultural philosophy has proposed since the nineties emphasizes what Raúl Fornet-Betancourt called “quality of coexistence” or conviviality. In this paper, we go deeper into these ideas, showing the implications and challenges that the understanding of interculturality has had in Chile, in one way or another. © 2024. Universidad de San Buenaventura Cali.